Perancangan Website E-Commers SRC Bunda Untuk Media Penjualan Produk - Nasywa Adillah; Desi Fauziah Bahri; Sularno Sularno; Zulfitri Yani (CV. ITTC INDONESIA, 2025)
The design of the SRC Bunda e-commerce website was carried out to simplify and modernize the buying and selling process in stores. In the current digital era, people's shopping habits have changed a lot. Many customers prefer to shop online because it is considered more practical, time-saving and flexible. Seeing these changes, SRC Bunda as a grocery store that sells daily necessities is trying to adapt by implementing a web-based sales system. This website was developed using HTML, CSS, and JavaScript by displaying the main features in the form of product search, product categories, and a shopping basket that is connected directly to WhatsApp to simplify the ordering process. The design process focuses on ease of use, an attractive interface, and ease of access on various devices such as laptops and smartphones. The implementation results show that the website can run well, the visual appearance is attractive, and the navigation is easy to understand by users from various groups. With this website, it is hoped that store sales will increase, service to customers will become more efficient, and be able to support the digitalization of MSMEs so they can compete in the modern market.